One Health Core Competency Domains - Frankson, Rebekah; Hueston, William; Christian, Kira; Olson, Debra; Lee, Mary; Valeri, Linda; Hyatt, Raymond; Annelli, Joseph; Rubin, Carol (Frontiers in Public Health, 2016)
The emergence of complex global challenges at the convergence of human, animal, and environmental health has catalyzed a movement supporting “One Health” approaches. Despite recognition of the importance of One Health approaches to address these complex challenges, little effort has been directed at identifying the seminal knowledge, skills, and attitudes necessary for individuals to successfully contribute to One Health efforts. Between 2008 and 2011, three groups independently embarked on separate initiatives to identify core competencies for professionals involved with One Health approaches. Core competencies were considered critically important for guiding curriculum development and continuing professional education, as they describe the knowledge, skills, and attitudes required to be effective. A workshop was convened in 2012 to synthesize the various strands of work on One Health competencies. Despite having different mandates, participants, and approaches, all of these initiatives identified similar core competency domains: management; communication and informatics; values and ethics; leadership; teams and collaboration; roles and responsibilities; and systems thinking. These core competency domains have been used to develop new continuing professional education programs for One Health professionals and help university curricula prepare new graduates to be able to contribute more effectively to One Health approaches.